Who owns what in Macondo?: the flexibilization of the rules of evidence in land restitution in Colombia - Ruiz González, Luis Enrique (International journal of transitional justice, 2021)
Land restitution programmes, as part of transitional justice systems, make victims face obstacles to prove their material and legal relationship with their dispossessed land. The literature suggests that these obstacles can be overcome by changing the rules of evidence, such as reversing the burden of proof, introducing different legal presumptions and adopting alternative forms of evidence. In Colombia, the Land Restitution Law introduced changes to the rules of evidence for processing land restitution claims. In this article, we claim that this flexibilization of the rules of evidence is essential to guarantee the restitution of property rights to victims, based on a comparison of the evidentiary rules that must be fulfilled by the victims of land dispossession under two transitional justice systems, both of which have been implemented in Colombia in recent years.